Avtobiografija in naratologija - Koron, Alenka (Jezik in slovstvo, 2008)
Following from the possibilities of the productive interaction of post-classical narratology, i.e. the most recent narrative theory approaches, the theory of autobiography and contemporary theories of fiction, I attempt inthe article to shed light on the philosophical and theoretical-methodological assumptions of certain contemporary narratological categories and models, while demonstrating their applicability to the researchof autobiographical narrative with the aid of some examples from Slovene literature.
Keywords: autobiography; avtobiografija; Cankar, Ivan: Moje življenje; literarna teorija; literary theory; naratologija; narratology; Slovene literature; slovenska književnost